Performance Characterization of Solid Oxide Cells Under High Pressure1. Issue 5 (2nd July 2015) - Sun, X.; Bonaccorso, A. D.; Graves, C.; Ebbesen, S. D.; Jensen, S. H.; Hagen, A.; Holtappels, P.; Hendriksen, P. V.; Mogensen, M. B.; Christiansen, Niels; Hagen, Anke; Bele, Petra; et al.
Abstract In this work, recent pressurized test results of a planar Ni‐YSZ (YSZ: Yttria stabilized Zirconia) supported solid oxide cell are presented. Measurements were performed at 800 °C in both fuel cell and electrolysis mode at different pressures. A comparison of the electrochemical performance of the cell at 1 and 3 bar shows a significant and equal performance gain at higher pressure in both fuel cell mode and electrolysis mode. Electrochemical impedance spectroscopy revealed that the serial resistance was not affected by the operation pressure; all the other processes that are dependent on partial pressures (oxygen, steam and hydrogen) were affected by increasing the pressure. In electrolysis mode at low current density, the performance improvement was counteracted by the increase in open circuit voltage, but it has to be borne in mind that the pressurized gas contains higher molar free energy.